2010
DOI: 10.5614/itbj.eng.sci.2010.42.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Shear Link of WF Section with Diagonal Web Stiffener of Eccentrically Braced Frame (EBF) of Steel Structure

Abstract: This paper presents results of numerical and experimental study of shear link behavior, utilizing diagonal stiffener on web of steel profile to increase shear link performance in an eccentric braced frame (EBF) of a steel structure system. The specimen is to examine the behavior of shear link by using diagonal stiffener on web part under static monotonic and cyclic load. The cyclic loading pattern conducted in the experiment is adjusted according to AISC loading standards 2005. Analysis was carried out using n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
9
0
2
Order By: Relevance
“…To reduce this, it can be controlled by placing web stiffeners on the link beam although it is not very efficient because of the influence of torque. Yurisman et al [14] and Budiono et al [4] perform experimental testing and numerical analysis of short-link beam elements (shear links) and long links (bending links) using diagonal web diagonals (diagonal web stiffeners). Suswanto [2] said Link with classification as a short link, will have a higher ductility than the long link.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this, it can be controlled by placing web stiffeners on the link beam although it is not very efficient because of the influence of torque. Yurisman et al [14] and Budiono et al [4] perform experimental testing and numerical analysis of short-link beam elements (shear links) and long links (bending links) using diagonal web diagonals (diagonal web stiffeners). Suswanto [2] said Link with classification as a short link, will have a higher ductility than the long link.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers showed some variation in results related to long links indicated that its performance could still be improved. Berman [11], Danesmand [5], Mohebkhah [12], Okazaki [13] and Yurisman [14] suggest that the value of the rotation and strength can be increased which improves the overall performance of the long links. Rotation of the link can still exceed the minimum threshold required, 0.02 rad, and the overstrength can exceed 1.0.…”
Section: Introductionmentioning
confidence: 99%
“…Mohebkhah [12] found an average overstrength value of 1.4 with inelastic rotation ranging from 0.04 to 0.09 rad. However, the weakness in the long link is caused by the formation of a plastic hinge on the flange in the welding zone at the end of the link with is then accompanied by failure caused by lateral torsional buckling, and fracture and buckling of the flange [4], [5], [9], [12], [14], [16], [17], [18], [19]. Some researchers suggested that avoid this weakness through limiting the slenderness of the flange.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations